Diapycnal mixing processes and vertical velocities within mesoscale structures - Estrada Allis,Sheila Natali (2016)
Programa de doctorado: Oceanografía Los procesos de mezcla diapicna, como el fenómeno de intrusión o entrainment (we), ejercen un importante control sobre el ecosistema marino y sus efectos pueden verse amplificados estructuras de mesoescala como remolinos y filamentos de afloramiento. Su estudio y el de los procesos de transporte vertical aún representan un desafío para la oceanografía debido a la naturaleza intermitente de la turbulencia y a la dificultad en las medidas a micro escala. La presente tesis trata con el estudio de las fuentes de energía cinética turbulenta (ECT), así como con los componentes que fuerzan el campo de velocidades verticales (w) dentro de dos estructuras de mesoescala del Atlántico norte. Diapycnal mixing processes such as diapycnal entrainment (we), by which fluid less turbulent from pycnocline is incorporated within the mixed layer, significantly control such systems and their effects can be amplified within mesoscale structures such as eddies and upwelling filaments. Despite the progress made in recent decades, the study of turbulent mixing and vertical transport processes is still a challenge in oceanography, partly due to the inherent intermittent nature of turbulence and the difficulty in taking measurements at fine- and micro-scales. This thesis examines the sources of turbulent kinetic energy (TKE) through the entrainment process, as well as the forcing components that dominate the vertical velocity (w) field within two mesoscale structures of the North Atlantic. Contiene resumen en español